2021
DOI: 10.1055/a-1341-9530
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of COVID-19 Among Children and Adolescents While Easing Lockdown Restrictions in Cologne, North Rhine-Westphalia, Germany

Abstract: Background In Germany, widespread full closures of schools and day care facilities were part of lockdown measures to control the spread of coronavirus disease 2019 (COVID-19). In the state of North Rhine-Westphalia closures took place on March 16, 2020 and were gradually eased from end of April 2020 until beginning of June 2020. Objective This study aims to evaluate the prevalence of COVID-19 among children and adolescents during the reopening period of schools and day care facilities in Cologne, North Rhine-W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…Throughout the pandemic PCR tests for acute illness were performed based on capacities of hospitals, schools, or private companies. By the end of 2022, PCR testing in Germany was largely reduced to a minimum of cases with severe hospitalization [18]. We discuss that while setting the inclusion criteria to positive PCR testing clearly limits the number of patients in an already limited collective of children, it still serves as a clear link of PCC to acute COVID-19 illness to investigate any organ dysfunctions or immune dysregulation that is the purpose of this study.…”
Section: General Cohort Characteristics In Pediatric and Adolescent Pccmentioning
confidence: 99%
“…Throughout the pandemic PCR tests for acute illness were performed based on capacities of hospitals, schools, or private companies. By the end of 2022, PCR testing in Germany was largely reduced to a minimum of cases with severe hospitalization [18]. We discuss that while setting the inclusion criteria to positive PCR testing clearly limits the number of patients in an already limited collective of children, it still serves as a clear link of PCC to acute COVID-19 illness to investigate any organ dysfunctions or immune dysregulation that is the purpose of this study.…”
Section: General Cohort Characteristics In Pediatric and Adolescent Pccmentioning
confidence: 99%
“…At the time, increasing evidence has shown that paediatric patients only have a moderate impact on the pandemic activity. The successive reopening of schools and day-care facilities has not been associated with a significant increase of the incidence of SARS-CoV-2 infection among children [15].…”
Section: Discussionmentioning
confidence: 96%